A revised technique for fabrication of hollow mandibular denture: A solution to severely resorbed residual ridge - Varun Baslas; Simranjeet Kaur; Kamleshwar Singh; Himanshi Aggarwal; Pradeep Kumar (Wolters Kluwer Medknow Publications, 2015)
Purpose: Prosthodontic rehabilitation of elderly patients with severely resorbed ridges is difficult due to compromised ridge height, increased inter-arch distance and altered insertion of associated jaw muscles. Planning dentures in such cases often require dentures that are lightweight to reduce the risk of further ridge resorption, which could otherwise complicate the situation. The purpose of the present technique is to fabricate a light weight lower denture by a revision of previously described technique in the literature. Materials and Methods: This article elucidates a simple technique for the fabrication of lightweight denture (hollow denture) in elderly patients with severely resorbed mandibular ridge. The minimum thickness of denture base acrylic resin for structural durability is ensured by a wax shim of 2 mm. The adequate hollow space indenture for optimal weight reduction is created by condensation silicone impression material. Conclusion: Condensation silicone putty material can be successfully used as a spacer for hollow dentures to combat severe ridge resorption.